On the synchronization of finite state automata (2019)
Abstract: We study some problems related to the synchronization of finite state automata and the Cˇerny’s conjecture. We focus on the synchronization of small sets of states, and more specifically on the synchronization of triples. We argue that it is the most simple synchronization scenario that exhibits the intricacies of the original Cˇerny’s scenario (all states synchronization). Thus, we argue that it is complex enough to be interesting, and tractable enough to be studied via algo- rithmic tools. We use those tools to establish a long list of facts related to those issues. We observe that planar automata seems to be representative of the synchroniz- ing behavior of deterministic finite state automata. Moreover, we present strong evidence suggesting the importance of planar automata in the study of Cˇerny’s conjecture. We also study synchronization games played on planar automata. We prove that recognizing the planar games that can be won by the synchronizer is a co-NP hard problem. We prove some additional results indicating that pla- nar games are as hard as nonplanar games. Those results amount to show that planar automata are representative of the intricacies of automata synchronization.